2004
DOI: 10.1111/j.0013-8703.2004.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual and olfactory cues for mate orientation behaviour in male white‐spotted longicorn beetle, Anoplophora malasiaca

Abstract: Olfactory and visual cues were shown to mediate short-distance orientation in Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae). In a laboratory test, more than 80% (n = 42) of males walked straight upward when presented with an untreated surface with a 75 ° slope. When a freshly killed female was fixed at a short distance (10 cm ahead and 5 cm to left/right) from the starting point, 50% of males (n = 30) were oriented toward the female before direct contact. Similar behavioural responses were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
(17 reference statements)
2
32
0
Order By: Relevance
“…As we previously reported, male A. malasiaca can orient to females at close range using both olfactory and visual cues derived from females, and the former is essential (Fukaya et al, 2004). In this study, we reveal that the female also locates males 66 M. FUKAYA et al 1.62 log 10 (doseME), white: ln(p/(1Ϫp))ϭϪ1.28ϩ1.62ϫ log 10 (doseME).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…As we previously reported, male A. malasiaca can orient to females at close range using both olfactory and visual cues derived from females, and the former is essential (Fukaya et al, 2004). In this study, we reveal that the female also locates males 66 M. FUKAYA et al 1.62 log 10 (doseME), white: ln(p/(1Ϫp))ϭϪ1.28ϩ1.62ϫ log 10 (doseME).…”
Section: Discussionsupporting
confidence: 56%
“…In some cerambycids, evidence of volatile pheromone that acts over short and/or long distances for mate location has been shown (Iwabuchi, 1982(Iwabuchi, , 1985Sakai et al, 1984;Wang et al, 1991;Fauziah et al, 1992;Kim et al, 1992;Zhang et al, 2002). In addition to such olfactory cues, visual orientation is likely to be involved in mate location in some cerambycids (Iwabuchi, 1985;Fukaya et al, 2004). Nevertheless, there have been only a few studies clarifying the importance of visual cues associated with olfactory cues in mate location, even in other insects (Shorey and Gaston, 1970;Hidaka, 1972;Wall, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such visual cues had been considered to be less important than olfactory cues. Recent studies on Anoplophora malasiaca, however, showed visual stimuli apparently enhanced mate location behavior when synergistically matched with olfactory cues when black, white and transparent glass-rod models were compared (Fukaya et al, 2004a(Fukaya et al, , 2005. Synergistic effects of visual and olfactory cues are also reported in a scarab beetle Holotrichia loochooana loochooana, wherein olfactory cues effect male location of females in the vicinity, and visual cues allow males to land directly on female (Fukaya et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…In Cerambicidae, it has also been suggested that mate body sizes (e.g. McLain and Boromisa, 1987;Hanks et al, 1996;Fukaya, 2004;Fukaya et al, 2004a), colors (Wang, 2002), shapes (Fukaya and Honda, 1996;Fukaya, 2004) and movement (Iwabuchi, 1985) influence mate location and mating success. Such visual cues had been considered to be less important than olfactory cues.…”
Section: Introductionmentioning
confidence: 99%